Theology and Social Empowerment of Marginal Subcultures: A Study on Pondok Tasawuf Underground Jakarta - Hasby, Muhammad Subky; Arifin, Syamsul; Kholish, Moh. Anas; Suroiyah, Evi Nurus (Islam Realitas: Journal of Islamic and Social Studies, 2024)
This study examines the theological principles underlying the social empowerment efforts implemented for the punk community at Pondok Tasawuf Underground Jakarta, focusing on articulating theological values in the context of empowerment and their implementation in daily life. Employing a qualitative phenomenological approach, several data in this study were collected through in-depth interviews with the founder and members of the punk community, participatory observation, and document analysis. The findings reveal that the theological principles underlying empowerment at Pondok Tasawuf Underground are rooted in holistic hijrah, encompassing both spiritual and social transformation. The "Roadmap to Return" program serves as the core agenda, consisting of two main paths: the Roadmap to Return to Allah, which emphasizes religious education and spiritual awareness, and the Roadmap to Return to Family, which underscores social responsibility and family relationship restoration. The principle of human equality serves as the theological foundation of this empowerment effort, affirming the universal dignity of every individual regardless of their background. The implementation of the theology of empowerment includes skill training, social assistance, and spiritual strengthening, significantly transforming the punk community from a marginalized group into productive individuals.